(untitled) (Mustansiria Dental Journal, 2018)
Background:The synergism between the action of non-steroidal anti-inflammatory drugs (NSAIDS) and steroids suggest that co-therapy may provide beneficial inflammatory and pain relief in the absence of side effects. The aim of the study was to compare the effect of co-administered dexamethasone and diclofenac sodium (diclofenac Na) with diclofenac Na alone on the postoperative pain, swelling and trismus after surgical removal of third molars. Methods:A prospective randomized study was conducted at the clinic of Oral and Maxillofacial Surgery, Dentistry College/ Mustansirya University. A total of 30 patients were randomly divided into two treatment groups, the first were given dexamethasone (30 minutes preoperative 8 mg and postoperative 4 mg IV 6 hours postoperatively in two doses) and oral dose of diclofenac Na 50 mg 30 minutes before and after surgery, while the second group were given 50 mg diclofenac Na orally alone 30 minutes before and after surgery (as with first group). The overall analgesic effect of the drug was assessed postoperatively by determination of pain severity using a category rating scale. Facial swelling was measured using a tape measure placed from tragus to gonion to tragus, while interincisal mouth-opening of patients was measured using a calibrated vernier pre-operatively and post-operatively. Results:Co-administration of dexamethasone and diclofenac Na was significantly superior to diclofenac alone for the relief of pain (P < 0.05), and facial swelling up to 48 hour postoperativly (P < 0.05). However, there was no significant difference for trismus relief between the two medication protocols (P > 0.05). Conclusion:This study shows enhanced effects of co-administered dexamethasone and diclofenac Na on short-term post-operative pain and swelling, compared to diclofenac sodium alone in third molar surgery